2021
DOI: 10.1029/2020jg006026
|View full text |Cite
|
Sign up to set email alerts
|

A 4,300‐year History of Dietary Changes in a Bat Roost Determined From a Tropical Guano Deposit

Abstract: • Bat foraging habits can be studied by analyzing their guano for sterols, stanols, and stable isotopes of carbon and nitrogen. • The diets of frugivorous, nectarivorous, and sanguinivorous bats were well-characterized by the sterol and stanol ratios in their guano. • We examined the composition of a 4,300-year-old bat guano deposit and identified two periods of increased fruit-based foraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Lacustrine environments (i.e., standing water) are preferred, as the sediments tend to accumulate chronologically with minimal mixing, in contrast to those in fluvial environments (i.e., running water) (Smol, 2008). There is also a limited but growing body of literature using similar paleolimnological approaches on peat (Outridge et al, 2016;Davidson et al, 2018;Groff et al, 2020), directly from nests (Burnham et al, 2009), and on guano deposits themselves (Nocera et al, 2012;Gallant et al, 2020Gallant et al, , 2021. Next, the sample is collected using a sediment corer, which, in its simplest form, is a tube inserted into the sediment to retrieve an undisturbed vertical profile of sediment [see Glew et al (2001) for a detailed overview].…”
Section: What Is Paleolimnology?mentioning
confidence: 99%
“…Lacustrine environments (i.e., standing water) are preferred, as the sediments tend to accumulate chronologically with minimal mixing, in contrast to those in fluvial environments (i.e., running water) (Smol, 2008). There is also a limited but growing body of literature using similar paleolimnological approaches on peat (Outridge et al, 2016;Davidson et al, 2018;Groff et al, 2020), directly from nests (Burnham et al, 2009), and on guano deposits themselves (Nocera et al, 2012;Gallant et al, 2020Gallant et al, , 2021. Next, the sample is collected using a sediment corer, which, in its simplest form, is a tube inserted into the sediment to retrieve an undisturbed vertical profile of sediment [see Glew et al (2001) for a detailed overview].…”
Section: What Is Paleolimnology?mentioning
confidence: 99%
“…Cholesterol derivatives, such as cholestadienone and cholestadienol (Melendez et al, 2013 ), and coprostanol ( Figure 13D , Supplementary Table 2 ), suggest the occurrence of organics produced by animals, protozoa, and red algae (Volkman et al, 1998 ). In particular, the detection of cholestadienone (cholesta-3,5-dien-7-one) and cholestadienol (3β-cholesta-4,6-dien-3-ol) are derivatives from cholesterol that denote a low extent of degradation (Melendez et al, 2013 ), while coprostanol has been reported as a fecal degradation product found in mammals and birds feces (Harrault et al, 2019 ; Gallant et al, 2021 ). Among the samples, cholestadienol and coprostanol mainly occurred in samples 134–1 and 134–2, where speleothem fragments were present, whereas cholestadienone was dominant in sample 134–3, the sample with tuff-like material ( Supplementary Figures 2A–C , Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Locations of caves around the world where guano deposits have been studied. Red circle: our study site in Carajás, Brazil; Yellow circles: 1- Grand Canyon, Arizona, USA [5 , 6] ; 2- Eagle Creek Cave, Arizona, USA [7 , 8] ; 3- Tumbling Creek Cave, Missouri, USA [4] ; 4- Round Spring Cavern, Missouri, USA [9] ; 5- Mammoth Cave, Kentucky, USA [10] ; 6- Spring Cave, Alabama, USA [11] ; 7- Fern Cave, Alabama, USA [3] ; 8- Jackson Bay Cave Complex, Jamaica [12 , 13] ; 9- Schwallenburgh Cave, Jamaica [14] ; 10- Home Away from Home Cave, Jamaica [14] , [15] , [16] ; 11- Blanchard Cave, Eastern Caribbean [17] ; 12,13- Southeastern Spain [18 , 19] ; 14- Grotte XVI, France [20] ; 15- Măgurici Cave, Romania [21] , [22] , [23] ; 16- Ziditǎ Cave, Romania [24 , 25] ; 17- Gaura cu Muscǎ Cave, Romania [26 , 27] ; 18- Gura Ponicovei Cave, Romania [28] ; 19- Topolnița Cave, Romania [29] ; 20- Arnhem Cave, Namibia [30] ; 21- China [31] ; 22- Siju cave, India [32] ; 23- Eraaning Cave, India [33] ; 24- Batu Cave, Malaysia [34] ; 25- Niah Cave, Borneo [34] ; 26- Gangub Cave, Philippines [33] ; 27- Makangit Cave, Philippines [34 , 35] ; 28- Tabon Cave, Philippines [36] ; 29- Gomantong Cave, Indonesia [37] ; 30- Bau Cave, Indonesia [36] ; 31- New Zealand [38] ; 32- New Zealand [39] . …”
Section: Methods Detailsmentioning
confidence: 99%